Geometric reliability model of the five site redundant structure - Usenko, Valery (Array, 2020)
The study results from the graphical representation on connectivity probability of systems that have structural redundancy for modeling. The structural reliability of different systems is presented. A oneparameter expression of a two-ring structure reliability with five sites is described. All the unique operating conditions of the structure are shown in a graphical form. The compact form of the exact expression of the redundant two-ring structure reliability with five sites is presented, which is convenient for computer modeling. The peculiarities of the dependences of many variables in the reliability model of the two-ring structure with five sites and four nodes are determined. It is shown that the graphic representation of the dependence of the five variables helps to study the properties of multiparameter dependencies. The components of a geometric model of various dimensions are considered in detail.